Pharmacokinetic comparison of a fixed-dose combination of telmisartan/rosuvastatin/ezetimibe/amlodipine 80/20/10/5 mg and a loose-dose combination of ezetimibe/rosuvastatin 10/20 mg and telmisartan/amlodipine 80/5 mg in healthy male subjects - Lee, Sooyoun; Kim, Hyun Chul; Kim, Kyung Tae; Kang, Seung-Hyun; Lee, SeungHwan; Yu, Kyung-Sang; Lee, Soyoung (Naunyn-Schmiedeberg's archives of pharmacology, 2025)
This study aimed to compare the pharmacokinetic (PK) profiles of a fixed-dose combination (FDC) tablet of telmisartan/rosuvastatin/ezetimibe/amlodipine 80/20/10/5 mg and a loose-dose combination (LDC) of two FDC tablets, ezetimibe/rosuvastatin 10/20 mg and telmisartan/amlodipine 80/5 mg, in healthy Korean male subjects. This study was conducted as a randomized, open-label, two-sequence, four-period crossover study. The subjects received the FDC or the LDC of telmisartan, rosuvastatin, ezetimibe, and amlodipine twice, with a 21-day washout in each period. Each sequence was composed of either FDC/LDC/FDC/LDC or LDC/FDC/LDC/FDC in that order. Serial blood samples for PK analysis were collected up to 48 h after rosuvastatin dosing and 72 h after telmisartan, ezetimibe, and amlodipine dosing. The PK parameters were calculated by a noncompartmental method, and safety profiles were evaluated throughout the study. Fifty-four healthy Korean male subjects were enrolled, and 42 subjects completed the study. The concentration‒time profiles of telmisartan, rosuvastatin, ezetimibe, and amlodipine were similar between the FDC and LDC groups. For each compound, the geometric mean ratios (90% confidence intervals) of the peak concentration and area under the plasma concentration‒time curve of FDC to LDC were within the conventional bioequivalence criteria of 0.8–1.25. Both the FDC and LDC treatments were well tolerated and determined to be safe. The FDC and LDC treatments with telmisartan, rosuvastatin, ezetimibe, and amlodipine showed pharmacokinetic bioequivalence, indicating that the FDC of telmisartan/rosuvastatin/ezetimibe/amlodipine 80/20/10/5 mg can be used as an alternative to the LDC treatment.